Differential expression of novel metabolic and immunological biomarkers in oysters challenged with a virulent strain of OsHV-1. (August 2017) - Young, Tim; Kesarcodi-Watson, Aditya; Alfaro, Andrea C.; Merien, Fabrice; Nguyen, Thao V.; Mae, Hannah; Le, Dung V.; Villas-Bôas, Silas
Abstract: Early lifestages of the Pacific oyster ( Crassostrea gigas ) are highly susceptible to infection by OsHV-1 μVar, but little information exists regarding metabolic or pathophysiological responses of larval hosts. Using a metabolomics approach, we identified a range of metabolic and immunological responses in oyster larvae exposed to OsHV-1 μVar; some of which have not previously been reported in molluscs. Multivariate analyses of entire metabolite profiles were able to separate infected from non-infected larvae. Correlation analysis revealed the presence of major perturbations in the underlying biochemical networks and secondary pathway analysis of functionally-related metabolites identified a number of prospective pathways differentially regulated in virus-exposed larvae. These results provide new insights into the pathogenic mechanisms of OsHV-1 infection in oyster larvae, which may be applied to develop disease mitigation strategies and/or as new phenotypic information for selective breeding programmes aiming to enhance viral resistance. Graphical abstract: Highlights: Herpesvirus-induced metabolic responses were investigated in oyster larvae by GC-MS. Host metabolism changes are suggestive of Irg-1-like activation. Energy and lipid metabolism was substantially disturbed during infection. Activation of immunoresponsive gene 1 and the Warburg effect is hypothesised. Metabolomics is a powerful approach to study disease in early oyster life stage.